Subject Positions and Interfaces : the Case of European Portuguese. - Costa, João (Studies in Generative Grammar SGG., 2004)
European Portuguese, like other Romance languages, display a great amount of word order variation. Out of the six logically possible permutations between Subject, Verb and Complement in a transitive sentence, five are possible: SVO, VSO, VOS, OVS and OSV.